Host selection and distribution of Dendrobium okinawense, an endangered epiphytic orchid in Yambaru, Japan. Issue 5 (15th May 2018) - Abe, Shin; Kotaka, Nobuhiko; Takashima, Atsushi; Abe, Tetsuto; Saito, Kazuhiko; Masaki, Takashi
Abstract: We investigated the epiphytic habit and distribution of Dendrobium okinawense, an endangered orchid in Yambaru (northern Okinawa), Japan. Fifty individuals of D. okinawense were detected on 46 host trees. From the canopy size in chronological aerial photographs, the habitat stands where D. okinawense was found were estimated to be mature. Host trees tended to have larger diameters. The most common host species was Castanopsis sieboldii, which dominates in Yambaru; several other tree species were described as hosts for the first time to our knowledge. However, the orchid was mainly associated with one of these, Distylium racemosum, irrespective of this tree's small basal area relative to other trees. We attribute this preference by D. okinawense to the external form and longevity of D. racemosum . The presence of D. okinawense and its host D. racemosum with large diameter is a good indicator of the existence of old‐growth forests containing endemic rare species in Yambaru.